The role of thoracodorsal artery perforator flap after breast conserving surgery - El-Gapaty, Fatemah; Skaker, Shawky; Sabry, Ahmed; Taalab, Ahmed (International Surgery Journal, 2021)
Background: The emergence of thoracodorsal artery perforator flap combined with radiotherapy as new techniques in breast reconstruction has resulted in greater focus on oncoplastic breast surgery. In this study, were to study the role of thoracodorsal artery perforator flap after breast conserving surgery. Methods: This study included 40 patients of stage I and II breast cancer at Menoufia University hospital from July 2018 to February 2019. Every patient accepted to be enrolled in thus study with curative intent by having breast conservative surgery and immediate reconstruction by TDAP flap. Results: The mean operative time was 145 min. Seroma is the commonest complication following TDAP flap reconstruction and occurred in four cases (20%) and was treated by repeated aspiration. The cosmetic outcome was acceptable with 90% of patients rating their outcome as either pleased or satisfied. The subjectively assessed functional outcome showed a mean time of 10 days postoperative for patients to regain their full range of shoulder movements. Conclusions: Thoracodorsal artery perforator flap can play a significant role in oncoplastic surgery and breast reconstruction with acceptable cosmetic and functional outcome.